Terapi holistik terhadap pecandu narkoba - Muhammad Ilham Bakhtiar; Suehartono Syam (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
This study aims to determine how the application of holistic therapy against drugaddicts at the Rehabilitation Center BNN Baddoka Makassar. This research is qualitative research with descriptive analysis, data processing and data analysis using data reduction, data presentation, and conclusion. The results of this study indicate that in the application of holistic therapy conducted at the Rehabilitation Center BNN Baddoka Makassar divided into 2, namely the weighting in the medical and medicines in the non-medical, in the medical section there are two phases of detoxification phase and entry-unit and treatment in the field Non-medical there are two phases of the primary phase and re-entry in the primary phase of the focus of treatment is social, psychological and religion in this phase there are 4 stages of the stage induction, younger, middle and older. Inhibiting factors are residen type factor, human resources, and resident personality, while the solution for resident type is applied outpatient, then for human resources use group system and personal resident solution in need of psychologist sensitivity.